War on poverty - Aggarwal, S.C. (Delhi, 2007)
Role Of The Privileged People What needs to done by the privileged individuals to eradicate poverty from their native villages is focussed in this book. These individuals, from any walk of life, if make a determined attack on poverty, can change the life style of weaker and poorer segments of population. The author has discussed the innovative and practical strategies to tackle the problem of poverty through people s participation. The book should be useful to all those who are really concerned and worried for the poor.
Keywords: Poverty